Blood Vessels and Lymphatic Vessels in the Cornea and Iris After Penetrating Keratoplasty. Issue 6 (June 2019) - Li, Suxia; Li, Lin; Zhou, Qingjun; Gao, Hua; Liu, Mingna; Shi, Weiyun
Abstract : Purpose: To detect early growth of blood and lymphatic vessels in the mouse cornea and iris after penetrating keratoplasty. Methods: Penetrating keratoplasty was performed with C57BL/6 mice as donors and BALB/c mice as recipients. Graft transparency and neovascularization were examined by slit-lamp microscopy. Whole mounts of the cornea and iris were processed for detection of the outgrowth of blood and lymph vessels. Results: On day 3 after surgery, all corneal grafts were slightly edematous, and blood vessels in the corneoscleral limbus dilated. LYVE-1 + lymphatic vessels and CD31 + blood vessels were distributed in the peripheral cornea. In the iris, the density of blood vessels increased, and LYVE-1 + cells nearly vanished. On day 7, the grafts became opaque, and blood vessels grew into the recipient bed. A great quantity of lymph vessels invaded the cornea. LYVE-1 + arborescent cells were found around the lymphatic vessels. In the iris, blood vessels became bulky and stiff, and arborescent LYVE-1 + cells increased in number. On day 14, corneal neovascular regression and graft clarity were found. Lymphatic vessels regressed more slowly than blood vessels in the cornea. In the iris, blood vessels remained coarse. Increasing arborescent LYVE-1 + cells were also noted in the ciliary body. Conclusions: Our findings suggest that the iris–ciliary body could amplify immune signals and in part promote initiation of immune rejection after keratoplasty by providing a pathway for macrophages, which might participate in corneal lymphangiogenesis.